Pengaruh Pengembangan Karir, Pelatihan, dan Komunikasi terhadap Produktivitas Karyawan pada PT Sinergi Gula Nusantara Pesantren - Nazhifa Shalsabilla; Lina Saptaria; Anita Sumelvia Dewi (MAMEN: Jurnal Manajemen, 2025)
PT. Sinergi Gula Nusantara Pesantren faces specific challenges in maintaining employee productivity. This study aims to analyze the influence of career development, training, and communication on employee productivity. This type of research is quantitative with a survey approach and uses a population of 139 employees. The sampling method is non-probability sampling with a saturated sample technique. The collected data were analyzed using various statistical tests, including validity and reliability tests, classical assumption tests (normality and heteroscedasticity), multiple linear regression analysis, coefficient of determination (R2) test, partial t-test, and simultaneous F-test. The results of the study indicate that: Partially, career development has a positive and significant influence on employee productivity (Sig. value 0.002 < 0.05). Training does not have a significant influence on employee productivity (Sig. value 0.178 > 0.05). Communication has a positive and significant influence on employee productivity (Sig. value 0.006 < 0.05). Simultaneously, career development, training, and communication all have a positive and significant influence on employee productivity (Sig. value 0.000 < 0.05). The novelty of this study lies in the analysis of the combination of career development, training, and communication variables in the specific context of the sugar processing industry. These findings provide new insights into the factors that directly influence productivity in this sector. The practical implications of this research are the importance for companies to improve career development programs and communication effectiveness to encourage optimal employee productivity, while the effectiveness of training programs needs to be further evaluated.